Differential Diagnosis of Akinetic Mutism and Disorder of Consciousness Using Diffusion Tensor Tractography: A Case Report - Byun, Dong Hyun; Jang, Sung Ho (Frontiers in Human Neuroscience, 2022)
This paper presents a case in whom a differential diagnosis of akinetic mutism with a disorder of consciousness was made using diffusion tensor tractography (DTT). A 69-year-old female patient was diagnosed with subarachnoid hemorrhage, intraventricular hemorrhage, and intracerebral hemorrhage produced by the subarachnoid hemorrhage. She exhibited impaired consciousness with a Coma Recovery Scale-Revised score of 13 until one month after onset. Her impaired consciousness recovered slowly to a normal state according to the Coma Recovery Scale-Revised (23 points: full score) at seven weeks after onset. On the other hand, she exhibited the typical clinical features of akinetic mutism (no spontaneous movement [akinesia] or speech [mutism]). On the DTT performed at one-month, the upper and lower dorsal ascending reticular activating systems, which are related to a disorder of consciousness, showed an almost normal state. In contrast, the prefronto-caudate and prefronto-thalamic tracts, which are related to akinetic mutism, showed severe injuries. These DTT results suggested that the patient’s main clinical features were not a disorder of consciousness but akinetic mutism. Therefore, DTT for the ascending reticular activating system, and the prefronto-caudate and prefronto-thalamic tracts could provide additional evidence for a differential diagnosis of DOC and AM at the early stages of stroke.